HY5: A Pivotal Regulator of Light-Dependent Development in Higher Plants - Xiao, Yuntao; Chu, Li; Zhang, Yumeng; Bian, Yeting; Xiao, Jiahui; Xu, Dongqing (Frontiers in Plant Science, 2022)
ELONGATED HYPOCOTYL5 (HY5), a bZIP-type transcription factor, acts as a master regulator that regulates various physiological and biological processes in plants such as photomorphogenesis, root growth, flavonoid biosynthesis and accumulation, nutrient acquisition, and response to abiotic stresses. HY5 is evolutionally conserved in function among various plant species. HY5 acts as a master regulator of light-mediated transcriptional regulatory hub that directly or indirectly controls the transcription of approximately one third of genes at the whole genome level. The transcription, protein abundance and activity of HY5 are tightly modulated by a variety of factors through distinct regulatory mechanisms. This review primarily summarizes recent advances on HY5-mediaed molecular and physiological processes and regulatory mechanisms on HY5 in model plant Arabidopsis as well as in crops.